2009
DOI: 10.1021/ja904447b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Optical Activity by Achiral Rod-Like Molecules Nanosegregated in the B4 Structure of Achiral Bent-Core Molecules

Abstract: Chirality in a mixture system consisting of bent-core 1,3-phenylene bis[4-(4-8-alkoxyphenyliminomethyl)benzoates] (P8-O-PIMB) and rod-like n-pentyl-cyanobiphenyl (5CB) molecules has been studied. Precise circular dichroism (CD) spectra using thin sample cells indicate mainly two characteristics: (1) the origin of CD signals is due to chiral-segregated bent-core molecules in the B(4) phase, where 5CB is in the isotropic phase; (2) the enhanced CD signal is detected in the B(X) phase, where 5CB is in the nematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
139
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 99 publications
(152 citation statements)
references
References 24 publications
11
139
1
1
Order By: Relevance
“…The surface energy and Dn calculations are then applied only to the remnant tail and the contribution of the pore to the average Dn is correspondingly reduced. In the same way, the larger pores contribute to the enhanced OR in 5CB/NOBOW systems observed by Otani et al 38 Smectic. At lower temperatures the nematic to smectic transition of the nanoconfined guests takes place, producing changes in both their bulk nematic and surface alignment behaviour, including a substantial increase in the pitch for chiral nematic guests in the larger pores.…”
Section: δN<0 δN<0supporting
confidence: 63%
See 1 more Smart Citation
“…The surface energy and Dn calculations are then applied only to the remnant tail and the contribution of the pore to the average Dn is correspondingly reduced. In the same way, the larger pores contribute to the enhanced OR in 5CB/NOBOW systems observed by Otani et al 38 Smectic. At lower temperatures the nematic to smectic transition of the nanoconfined guests takes place, producing changes in both their bulk nematic and surface alignment behaviour, including a substantial increase in the pitch for chiral nematic guests in the larger pores.…”
Section: δN<0 δN<0supporting
confidence: 63%
“…The nanofilaments can be aligned with self-assembled monolayers 33 , shearing 34 , topographic confinement 35 and controlled growth in a unidirectional director field 36 . Potential applications of HNFs utilize electric-field controlled optical activity in nano-segregated 5CB/HNF mixtures 37 , the enhanced optical activity of achiral, rod-like molecules nanosegregated in the HNF structure 38 or the self-assembled hydrophobic surfaces formed by toric focal conics and HNFs 39 . HNF networks can even form organogels that absorb large amounts of solvent at concentrations as low as 2 wt% (refs 40,41).…”
mentioning
confidence: 99%
“…While the dark conglomerate usually appears on cooling directly from the isotropic and changes to crystal at lower temperature, [11][12][13][14] the B4 filaments are quite stable and robust, with the properties of the phase preserved even on cooling to room temperature and in mixtures with calamitic LCs (Figure 1 e), [15] making B4 materials of potential use for chiral-optic materials. [16] Because of their twisted conformation, helical filaments cannot completely fill space near the interface with a flat substrate or make full contact with such a surface. This implies that the structure of the B4 phase must be modified at a liquid The B4 liquid crystal phase of bent-core molecules, a smectic phase of helical nanofilaments, is one of the most complex hierarchical self-assemblies in soft materials.…”
Section: Introductionmentioning
confidence: 99%
“…This helical nanofilament (HNF) phase is particularly interesting owing to its unique hierarchical nanostructure 7,8 in which the individual filaments further selforganize into oriented arrays of filaments that are phase coherent with respect to their twist. The bulk HNF phase expels most guest molecules, such as rod-shaped liquid crystals [9][10][11][12][13][14][15] , and their unique structure makes it attractive for the design of bulk and surface structures with controlled porosity and roughness at the nanometre and micrometre scales. For example, Kim et al 16 demonstrated a potential application of textured HNF surfaces as self-assembled super hydrophobic layers.…”
mentioning
confidence: 99%